PENGARUH KUALITAS PELAYANAN DISTRIBUSI AIR TERHADAP TINGKAT KELUHAN PELANGGAN PDAM TIRTA PAKUAN KOTA BOGOR TAHUN 2015 DAN TAHUN 2016 - Rustanti, R. Poppi; Alfianti, Desty (Jurnal E-Bis (Ekonomi-Bisnis), 2018)
This study aims to identify the quality of service provided by the company, to identify the complaints handling done by the company and to analyze the effect of the service quality of the company on the complaints experienced by the customers of PDAM Tirta Pakuan Bogor City. The method used in this research is quantitative by means of survey research. This research was conducted at PDAM Tirta Pakuan Bogor City, precisely at No. Siliwangi Street. 121 Bogor 16142, West Java. The sampling technique used in this research is nonprobability sampling technique by purposive sampling. Determination of the number of samples by Gay and Diehl (1992) and Kerlinger and Lee (2000). Validity and reliability test was submitted to 30 respondents with Product Moment formula from Pearson and Alpha Cronbach. Quantitative data are presented in the form of frequency tables. The statistical test was performed with SPSS program version 20 with Rank Spearman's correlation test and statistical test of multiple regression analysis. Based on the results of research shows that the service quality of Tirta Pakuan PDAM Kota Bogor is good. This is seen from the results of the distribution of research data showing the attitude of some respondents agree with the services provided by looking at customer complaints data that can be overcome by the company. The results of multiple regression analysis showed that the overall of each of the indicator variables give effect of 19.6% to the level of complaints experienced by customers with the value of r count more than 0.361 with a confidence level of 5% and the value of cronbach alpha greater than 0, 60.